An Optimized Wireless Network Architecture for Department of Agriculture, Region 1 - Goldara, Ruel; Patacsil, Joseph (Data Science: Journal of Computing and Applied Informatics, 2021)
In the emergence of the highly connected Internet of Things (IoT) and the rise of wireless network technologies, organizations are confronting expanded wireless network capability, stability, and reliability. Each organization that aims to manage wireless network services that customers and employees request must be robust, secured, and easy to manage, henceforth; optimized wireless network architecture ought to be a top priority. This study developed the optimized wireless network architecture for the Department of Agriculture, Region 1 to further provide a robust, more secure, and reliable wireless network design using a Prepare, Plan, Design, Implement, Operate and Optimize Methodology. The comparative and evaluative research design was used in determining the wireless network status of the current wireless network design of the Department of Agriculture, Region 1 into other agencies' wireless network designs and standards as well as the testing and implementation of the optimized wireless network architecture. Wireless network simulation and results of the wireless network design are interpreted using the Received Signal Strength Level (RSSL) and service coverage area. The testing of the optimized wireless network architecture shows that it is reliable, stable, robust, and secured and it is applicable in the agency.